Pelaksanaan Perlindungan Pekerja dalam Keselamatan dan Kesehatan Kerja di PT Tun Hong Garment Indonesia - Ricky Chrisandi Gunawan; Sapto Hermawan (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This research aims to determine the implementation of worker protection at PT Tun Hong Garment Indonesia, especially in terms of occupational safety and health and the obstacles that exist at PT Tun Hong Garment Indonesia in implementing occupational safety and health protection. This research belongs to a prescriptive normative legal research. The sources of law used are primary and secondary legal materials. The data analysis technique used in this legal research is to use the deduction method. The results of the analysis, it is known that the implementation of occupational safety and health protection at PT Tun Hong Garment Indonesia has not fully complied with the Regulation of the Minister of Manpower and Transmigration Number 8 of 2010, Government Regulation Number 50 of 2012 and Regulation of the Minister of Manpower Number 2 of 1980. PT Tun Hong Garment Indonesia as a company has not carried out its obligations in terms of inspecting personal protective equipment properly, has not implemented the Occupational Safety and Health Management System (SMK3) and has not carried out Periodic Health Checks, thus the rights granted by law are related to safety and Occupational Health for workers has not been fulfilled.